2021
DOI: 10.3390/biom11081253
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of MECP2E1-E2 Isoforms and BDNF by Metformin and Simvastatin through Analyzing Nascent RNA Synthesis in a Human Brain Cell Line

Abstract: Methyl CpG binding protein 2 (MeCP2) is the main DNA methyl-binding protein in the brain that binds to 5-methylcytosine and 5-hydroxymethyl cytosine. MECP2 gene mutations are the main origin of Rett Syndrome (RTT), a neurodevelopmental disorder in young females. The disease has no existing cure, however, metabolic drugs such as metformin and statins have recently emerged as potential therapeutic candidates. In addition, induced MECP2-BDNF homeostasis regulation has been suggested as a therapy avenue. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
(96 reference statements)
0
15
0
Order By: Relevance
“…In this regard, MeCP2 binding to methylated DNA resulted in a reduced rate of RNA polymerase II at the transcription start sites, which may lead to suppressed transcriptional initiation [ 100 ]. Of note, MeCP2 homeostasis regulation is through a regulatory network that involves BDNF-MeCP2 regulation [ 101 , 102 , 103 , 104 , 105 ]. The regulatory link of BDNF-MeCP2, in part, involves MeCP2 phosphorylation at specific serine residues that contribute in response to certain drugs [ 106 , 107 ].…”
Section: An Overview Of Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, MeCP2 binding to methylated DNA resulted in a reduced rate of RNA polymerase II at the transcription start sites, which may lead to suppressed transcriptional initiation [ 100 ]. Of note, MeCP2 homeostasis regulation is through a regulatory network that involves BDNF-MeCP2 regulation [ 101 , 102 , 103 , 104 , 105 ]. The regulatory link of BDNF-MeCP2, in part, involves MeCP2 phosphorylation at specific serine residues that contribute in response to certain drugs [ 106 , 107 ].…”
Section: An Overview Of Dna Methylationmentioning
confidence: 99%
“…Overall, MeCP2 harbors a robust role in brain function and progression towards neural developmental milestones, at the beginning of neuronal differentiation, and in mature neurons. Furthermore, MeCP2 is differentially expressed in a region-dependent manner and is cell type-specific-dependent in both human and murine brain/brain cells [ 42 , 43 , 44 , 45 , 46 , 47 , 73 , 101 , 102 , 104 , 114 ]. Given that MeCP2 participates in regulating dynamic gene expression, researchers have highlighted its vital involvement in neurobehavioral abnormalities that are linked to many complications such as metabolic impairments.…”
Section: An Overview Of Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies revealed that metformin improves expression and BDNF levels in experimental cerebral ischaemia in animal models via an AMPK‐dependent pathway 113,114 . Likewise, metformin improves age‐mediated neurocognitive impairment through the activation of BDNF/TrkB signalling 115 . Metformin has been shown to enhance neurogenesis and spatial memory formation in adult mice through increased phosphorylation of atypical protein kinase C (aPKC), activation of CREB binding protein (CBP) and activation of BDNF signalling 115 .…”
Section: The Mechanistic Role Of Metformin In Epilepsymentioning
confidence: 99%
“…The reason for this might be a longer period of developmental plasticity in humans, suggesting that MeCP2 might alter the expression of the genes important for neuronal development [ 30 , 39 ]. MECP2 is regulated both transcriptionally and post-transcriptionally [ 27 , 37 , 40 ].…”
Section: Introductionmentioning
confidence: 99%